2012
DOI: 10.2478/s13382-012-0023-9
|View full text |Cite
|
Sign up to set email alerts
|

Woodsmoke marker levoglucosan: Kinetics in a self-experiment

Abstract: Objectives: Concerns on climate change are leading to the renaissance of wood burning and particulate exposures. Levo glucosan is used as a marker of woodsmoke in air and urine. Objectives: Contribution of data on urinary excretion of levo glucosan, to improve biomonitoring and source apportionment of woodsmoke. Materials and Methods: 1, 3, 5, and 7 hours after 5 mg of levoglucosan had been administered orally, urinary excretion was measured by HPLC and mass spectrometry. Results: After oral intake, urine conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…59 Review of the nicotine levels in teabacco demonstrated that teabacco is on a similar scale to commercial tobacco with respect to (Z)-9-Octadecenamide Nicotine lozengedispersion aid in surface coatings. 43 Not toxic 1,6-Anhydro-β-D-Glucopyranose Bible paper and teapyrolysis of carbohydrates, such as starch 85 and cellulose 86,87 Not toxic, 44 excreted in urine 88…”
Section: Identification Of Compounds By Gc-msmentioning
confidence: 99%
“…59 Review of the nicotine levels in teabacco demonstrated that teabacco is on a similar scale to commercial tobacco with respect to (Z)-9-Octadecenamide Nicotine lozengedispersion aid in surface coatings. 43 Not toxic 1,6-Anhydro-β-D-Glucopyranose Bible paper and teapyrolysis of carbohydrates, such as starch 85 and cellulose 86,87 Not toxic, 44 excreted in urine 88…”
Section: Identification Of Compounds By Gc-msmentioning
confidence: 99%
“…Levoglucosan is generally considered non-toxic however its presence in biofluids, such as urine, has been suggested as a biomarker for WS exposure and thus exposure to more toxic compounds such as polyaromatic hydrocarbons 47 . However, levoglucosan has a short half-life in the body whereby >70% of it has been excreted within 7 hours of exposure 47 . Guaiacol, a methoxyphenol compound, is produced through the pyrolysis of lignin and has also been proposed as a marker of WS exposure.…”
Section: Discussionmentioning
confidence: 99%